ANALISIS PEMBELAJARAN ; MENUJU PEMBELAJARAN VIRTUAL REALITY BERBASIS PENDEKATAN KONSTRUKTIVIS DAN PENERIMAAN TEKNOLOGI - ' Nofri Hendri, Darmansyah, Fetri Yeni, J (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2020)
In the constructivist paradigm, Virtual Reality technology focuses on the active interactive learning process of learners and attempts to reduce the gap between learner knowledge and real life experiences. Recently, virtual reality technologies have been developed for various applications in education, but more research is needed to establish appropriate and effective learning techniques and practices to motivate meaningful learning. The results showed that self-efficacy and perceived interaction are two important factors affecting perceived ease of use, perceived usefulness and learning motivation. In addition, learning motivation is also a predictor for influencing perceived usefulness. After that, perceived ease of use, perceived usefulness, and motivation to learn are three important factors that influence students' intentions to use virtual reality learning environments.Keywords: virtual reality (VR), constructivism, technology acceptance model (TAM), perceived self-efficacy, learning motivation, perceived interaction